Kedudukan Badan Keamanan Laut dalam Penegakan Hukum di Laut - Yusuf, Hari Sugiharto; Sumardi, Juajir; Latif, Birkah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This research discusses the position of the Marine Security Agency in law enforcement at sea. This research uses a statutory approach and a historical approach. Descriptive qualitative analysis technique, namely by describing, explaining, describing, and describing primary legal materials and secondary legal materials following the problems closely related to this research, then drawing a conclusion based on the analysis that has been done. The results showed that the position of the Marine Security Agency (Bakamla) with fellow law enforcers at sea as a coordinator, but it does not eliminate the authority of other law enforcers. Bakamla is present to replace the function of the Marine Security Coordinating Agency (Bakorkamla) which was previously considered to fail in synergizing law enforcement at sea. Meanwhile, Bakamla's authority is to conduct instant pursuit, stop, inspect, arrest, bring ships, and hand over to related agencies. These authorities are authorities that are often found in the investigation process, but Bakamla as a law enforcer at sea, is not given the authority to conduct investigations. Bakamla's authority as an investigator is still waiting for the Omnibus Law on Marine Security which is currently being discussed in the House of Representatives.